Opportunities and challenges for use of minipigs in nonclinical pharmaceutical development: Results of a follow-up IQ DruSafe survey - David O. Clarke; Kaushik Datta; Kevin French; Michael W. Leach; Drew Olaharski; Susanne Mohr; Devon Strein; Jeanine Bussiere; Bianca Feyen; Beatrice E. Gauthier; Michael Graziano; Joanna Harding; et al. (Regulatory Toxicology and Pharmacology, 2024)

Pectobacterium atrosepticum (van Hall) Gardan et al. as a Causal Agent of Potato Blackleg in Greenland - Eigil de Neergaard; Susanne Harding; Robert Czajkowski (European Journal of Plant Pathology, 2020)
As a part of a blackleg and soft rot survey on potato plants cultivated in the agricultural region of Southern Greenland during the growing season of 2019 diseased potato plants and tubers were collected at six localities. Samples of plants and tubers with typical blackleg and soft rot symptoms were cut into parts weighing ca. 10–15 g each and incubated in potato enrichment broth (PEB) under anaerobic conditions for 4–7 days at ca. 20–22 °C (conditions during shipment of the samples from Greenland to Poland). After enrichment plant extracts were plated on crystal violet pectate (CVP) medium to isolate individual cavity-forming bacterial colonies. The inoculated plates were incubated at 22, 25 and 28 °C to maximize the chance of finding pectinolytic bacteria with different growth temperature optima. Cavity-forming isolates were collected and purified to pure cultures on tryptone soya agar (TSA). Ten cavity-forming isolates, named Green1 – Green10, representing isolates from symptomatic plants from different locations, were selected for analyses. The isolates gave a 434 bp. product in Pectobacterium spp.-specific PCR and a 439 bp. product in P. atrosepticum (Pba) -specific PCR. These isolates were Gram (−) rods, facultative anaerobic, catalase positive, oxidase and indole negative, grew in TSB + 5% NaCl, produced acid from lactose, maltose and raffinose. BlastN analyses of the ca. 1300 bp. 16S rDNA sequences of all 10 strains indicated a 99–100% similarity to the 16S rDNA of Pectobacterium atrosepticum . All 10 isolates caused soft rot of potato tuber slices after 72 h at 28 °C. Phylogenetic analysis based on the recA gene sequence grouped the isolates together with P. atrosepticum strains CFBP1526T and SCRI1043. This is the first report on isolation of P. atrosepticum from blackleg-diseased potato plants in Greenland. The presence of P. atrosepticum and its possible impact on potato cultivation in Greenland is discussed.

Hans Gocht (1930–2014) - James B. Riding; Susanne Feist-Burkhardt; Robert A. Fensome; Ian C. Harding; Jörg Pross (Palynology, 2015)

Modelling the potential impact of global warming on Ips typographus voltinism and reproductive diapause - Anna Maria Jönsson; Susanne Harding; Paal Krokene; Holger Lange; Åke Lindelöw; Bjørn Økland; Hans Peter Ravn; Leif Martin Schroeder (Climatic Change, 2011)

Living with the enemy: parasites and pathogens of the ladybird Harmonia axyridis - Helen E. Roy; Emma Rhule; Susanne Harding; Lori-Jayne Lawson Handley; Remy L. Poland; Eric W. Riddick; Tove Steenberg (BioControl, 2011)

Spatio‐temporal impact of climate change on the activity and voltinism of the spruce bark beetle, Ips typographus - ANNA MARIA JÖNSSON; GUSTAF APPELBERG; SUSANNE HARDING; LARS BÄRRING (Global Change Biology, 2009)
The spruce bark beetle Ips typographus is one of the major insect pests of mature Norway spruce forests. In this study, a model describing the temperature‐dependent thresholds for swarming activity and temperature requirement for development from egg to adult was driven by transient regional climate scenario data for Sweden, covering the period of 1961–2100 for three future climate change scenarios (SRES A2, A1B and B2). During the 20th century, the weather supported the production of one bark beetle generation per year, except in the north‐western mountainous parts of Sweden where the climate conditions were too harsh. A warmer climate may sustain a viable population also in the mountainous part; however, the distributional range of I. typographus may be restricted by the migration speed of Norway spruce. Modelling suggests that an earlier timing of spring swarming and fulfilled development of the first generation will significantly increase the frequency of summer swarming. Model calculations suggest that the spruce bark beetle will be able to initiate a second generation in South Sweden during 50% of the years around the mid century. By the end of the century, when temperatures during the bark beetle activity period are projected to have increased by 2.4–3.8 °C, a second generation will be initiated in South Sweden in 63–81% of the years. The corresponding figures are 16–33% for Mid Sweden, and 1–6% for North Sweden. During the next decades, one to two generations per year are predicted in response to temperature, and the northern distribution limit for the second generation will vary. Our study addresses questions applicable to sustainable forest management, suggesting that adequate countermeasures require monitoring of regional differences in timing of swarming and development of I. typographus , and planning of control operations during summer periods with large populations of bark beetles.

Biological and other alternative control methods against the woolly beech aphid Phyllaphis fagi L. on beech Fagus sylvatica seedlings in forest nurseries - Trine Iversen; Susanne Harding (Journal of Pest Science, 2007)